Old and new trades in peruvianisms dictionaries (1938-2015) - Luna, Rosa (2019)
The main objective of this study, of empirical, applied, and documental nature, was to analyze the lexicographic behavior displayed by the names of trades in the dictionaries of Peruavianisms. The sample of the study was formed by 525 trades extracted from thirteen lexicographic works on Peruavianisms, which were published between 1938 and 2015. The content analysis technique was applied in the data analysis and the descriptive statistics tables were designed with SPSS software.The study reached the following general conclusion: The lexicographic behavior of the trades in the dictionaries of Peruvianisms show a marked tendency to suffixal derivation with a considerable recurrenceof the -ero/-era suffixes. Semitransparency, reduced recurrence in dictionaries, and wide subject dispersion represented three additional characteristics identified in the lexicographic corpora of the study.